Evaluation of The Acute Toxicity of Three Locally Synthesized Dyes (3,5-Dimethoxypyrimidine Azo-6- Methyl Urazil, 5-Ethoxybenzothiazole Azobenzoloxyphenol and 4-Ethyl 5,2,3-Thiazole Azo-6-Methyl Uracil) Using Nitrosomonas Sp and Nitrobacter Sp - E, Akponah; J.O, Otutu; O.O, Akpomie; M, Ubogu (The Asia Journal of Applied Microbiology, 2014)
The acute toxicity of three dyes (3, 5-dimethoxypyrimidine azo-6- methyl urazil, 5-ethoxybenzothiazole azobenzoloxyphenol and 4-ethyl 5,2,3-thiazole azo-6-methyl of uracil were evaluated using Nitrosomonas and Nitrobacter. Standardized inoculum ofeach test organism was introduced into various logarithmic concentrations (0.01 to 100 mg/L) of the dyes for a period of 96 hours and cell mortality was used as index for assessment. Results obtained Indicated that the three dyes were inhibitory to the survival of the organisms. An increase in cell mortality (toxic response) of each organism with increase in concentration of the dyes and the duration of exposure was observed. The 96h LC50 values of 3,5-dimethoxypyrimidine azo-6- methyl urazil, 5-ethoxybenzothiazole azobenzoloxyphenol and 4-ethyl 5,2,3-thiazole azo-6-methyluracil to Nitrosomonas were 2.89,2.80 and 5.30 (mg/L) respectively. Similarly, the96h LC50 values of 3,5-dimethoxypyrimidine azo-6- methyl urazil, 5-ethoxybenzothiazole azobenzoloxyphenol and 4-ethyl 5,2,3-thiazole azo-6-methyl of uracil to Nitrobacter were 0.001, 0.20 and 1.11 respective;ly. Anaysis of variance at p = 0.05 showed thatthere was no significant difference in the response of Nitrosomonas to the various dyes. However, there was a significant difference in the response of Nitrobacter to the three dyes in the order 3,5-Dimethoxypyrimidine azo-6 - methyl uracil >5-Ethoxybenzothazole azobenzoloxyphenol>4-Ethyl 5,2,3-thiazole azo-6-methyl uracil. T-test also revealed that there were significant differences in the response of NitrosomonasandNitrobacterto the toxicity of each of the dye.